Rice field distribution in Aceh: A study in the context of spatial planning - Amri Ikhwan; Serlia Ayuli; Ardiati Aulia Syifa; Andika Yan; Al Tumus M. Galang Ramadhan; Hidayah Nurul (BIO Web of Conferences)
Rice farming is essential for meeting food consumption needs and significantly contributes to the regional economy of Aceh Province, Indonesia. This study aims to analyze the spatial distribution of rice fields and their alignment with spatial planning. The main data utilized include the map of primary paddy fields, recorded by official authorities in 2023, and the provincial-level spatial planning map. These datasets were overlaid using geographic information system tools to identify alignments and discrepancies between actual and planned land use. According to official data, rice fields cover an area of 202,811.38 ha, representing 3.5% of the province's total land area. The distribution is mainly concentrated along the northern and eastern coasts of mainland Aceh. Based on the overlay analysis, 23.6% of the existing rice fields were inconsistent with the spatial planning. Detailed percentages of these inconsistencies for each regency/city are provided in this article. The study emphasizes the importance of data-driven, adaptive planning approaches to improve agricultural policies, food security, and sustainable land management.